Academic Senate Minutes 2003-11-13 - Academic Senate:::::::::
Agenda amended and approved. Special Guest Mayor Armando Flores of Rohnert Park. Report of the Chair. Approval of minutes deferred. Consent items: Major changes from Physics – attachments; Revised concentration in Kinesiology – attachments; Applied Stats Minor in the Mathematics all approved. Campus Planning Committee nominations of Steve Orlick and Tom Jacobson approved. Information Item: End-of-Year reports: SAC, Academic Freedom. Lecturer's Resolution on Enterprises Surplus approved. From S&F: Conflict with By- Laws and Grade Appeal Policy first reading waived, approved. First reading from S&F: By- Laws change regarding replacement of officers. Report from Provost. First Reading from FSAC: Resolution on Lecturer's on Senate Compensation. APC report. Chair Nelson's reports on Academic Affair Strategic Planning process amended to the minutes.